PROSPEK PEMANFAATAN BIOPESTISIDA BAKTERI ENTOMOPATOGENIK ISOLAT LOKAL SEBAGAI AGEN PENGENDALI HAYATI HAMA TANAMAN SAYURAN - Salaki, Ch L; Tarore, D (EUGENIA, 2018)
The utilization efforts of entomopathogenic bacteria as an insecticide is still being developed. One of the pathogens with the potential to be developed as a source of insecticide is Bacillus spp. The study aims to determine the level of pathogenicity and the pathogenicity spectrum, as well as obtain isolates with high virulence against pests of vegetable crops to be used as a biopesticide candidates. Testing the power to kill larvae isolates of Bacillus thuringiensis against Crocidolomia pavonana, Plutella xylostella and Spodoptera litura performed by the method of Ohba and Aizawa. The results showed that of 21 local isolates B. thuringiensis, there were 15 isolates that could cause mortality of > 50% for the larvae of C. binotalis, 20 isolates against larvae of P. xylostella and 12 isolates against larvae of S. litura. LT50for treatment of B. thuringiensis in C. pavonana pests reached at 15.5 hours, at P. xylostella 10.2 hours and S. litura at 22.4 hours. Potential selected isolates based on their pathogenicity were then developed into biopesticide candidates to control pest Crocidolomia pavonana, Plutella xylostella and Spodoptera litura in vegetable crops